INTEGRASI KEUANGAN SOSIAL (ZISWAF) DAN BISNIS PESANTREN DALAM PEMBERDAYAAN SOSIAL-EKONOMI MASYARAKAT DI JAWA TIMUR - Faiza, Nurlaili Adkhi Rizfa; Syarifudin, Syarifudin; Nurafini, Fira (Jurnal Ekonomika dan Bisnis Islam, 2023)
The high number of Islamic Boarding School and the prominence of its alumni suggest that Pesantren have a lot of promise in terms of social change and economic empowerment for communities in the surrounding area. With the establishment of the Pesantren Business Holding (HEBITREN), One Pesantren One Product (OPOP), and Pesantren Sarekat Business Cooperative (KSBP) as part of the Islamic Boarding Schools independence development program in East Java, the development of the Islamic Boarding Schools business have begun to become a special focus. Islamic Boarding Schools also operate Islamic social finance institutions such as the Amil ZIS Institution (LAZIS) and Micro Waqf Banks (BWM), which can help the local economy. This study took a qualitative approach to the library, relying on scientific research of papers, journals, and relevant agency data. This research aims to provide a synthesis of efforts to develop an alternative model of community economic empowerment in East Java through the integration of social finance (ZISWAF) and business run by Islamic Boarding Schools. The finding of the study shows that the integration of social finance with the Islamic boarding school business is able to maximize the independence and quality of Islamic boarding school education, which contributes to the ummah's and nation's economic independence.